Metastatic Follicular Thyroid Carcinoma Secreting Thyroid Hormone and Radioiodine Avid without Stimulation: A Case Report and Literature Review - Syed A. Abid; Brendan C. Stack; Donald L. Bodenner (Case Reports in Endocrinology)
Introduction. This is an extremely rare case of a patient with metastatic follicular thyroid cancer who continued to produce thyroid hormone and was iodine scan positive without stimulation after thyroidectomy and radioiodine (I-131) therapy. Patient Findings. A 76-year-old Caucasian male was diagnosed with metastatic follicular thyroid carcinoma on lung nodule biopsy. Total thyroidectomy was performed and he was ablated with 160 mCi of I-131 after recombinant human thyrotropin (rhTSH) stimulation. Whole body scan (WBS) after treatment showed uptake in bilateral lungs, right sacrum, and pelvis. The thyroglobulin decreased from 2,063 to 965 four months after treatment but rapidly increased to 2,506 eleven months after I-131. Thyroid stimulating hormone (TSH) remained suppressed and free T4 remained elevated after I-131 therapy without thyroid hormone supplementation. He was treated with an additional 209 mCi with WBS findings positive in lung and pelvis. Despite I-131, new metastatic lesions were noted in the left thyroid bed and large destructive lesion to the first cervical vertebrae four months after the second I-131 dose. Conclusions. This case is exceptional because of its rarity and also due to the dissociation between tumor differentiation and aggressiveness. The metastatic lesions continued to secrete thyroid hormone and remained radioiodine avid with rapid progression after I-131 therapy.